Mange Mites of Goats in Malle District of South Omo Zone, Southern Ethiopia - Fesseha H (Dove Medical Press, 2021)
Haben Fesseha,1 Esmael Etana,2 Mesfin Mathewos1 1School of Veterinary Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2Malle District Veterinary Clinic, Malle, South Omo, EthiopiaCorrespondence: Haben Fesseha Email haben.senbetu@wsu.edu.etBackground: Mange mites are economically damaging goat ectoparasites that cause skin rejection or downgrading in Ethiopian tanneries and leather industries.Methods: A study was done on 384 randomly selected goats to identify the proportion of mites and potential associated factors in the Malle district of South Omo Zone, Ethiopia using a cross-sectional survey. A questionnaire investigation was also performed to evaluate the knowledge and preventative measures taken by goat owners during mange mites infection. A skin scraping was employed to collect mange mites for identification.Results: Out of 384 examined goats, 34.6% (133/384) of goats were infected with a variety of mange mite species. Demodex (2.86%), Psoroptes (8.1%), and Sarcoptes (23.7%) were the three mange mite genera identified in three sites of Malle district. Goats with poor body condition score (BCS) were the most infected (43.6%) with mange mites compared with moderate (39.1%) and good body condition (17.3%) goats. Adult goats (37.6%) were more infested than young (32.3%) and old (30.1%), whereas there was a higher infestation in males (60.2%) than females (39.8%). However, age, sex, and BCS of the goats had no significant (p > 0.05) correlation with the occurrence of mange mites. Skin lesion due to mange mites infection was most frequently observed on the head region (26.3%), followed by legs (24.8%) and thoracic region (22.6%). The questionnaire survey indicated that 86.27% of the participants preferred to use modern acaricides to control mange mites, while 97.4% of participants have been involved in government-sponsored deworming programs.Conclusion: Mange mites especially Sarcoptes species were major skin problems in goats in the study, so the owners should be advised to improve their management and use mite control in goats regularly in the area.Keywords: mites, goats, Malle district, prevalence, South Omo Zone